Expression profiling of potato germplasm differentiated in quality traits leads to the identification of candidate flavour and texture genes - Ducreux, Laurence J M (Journal of experimental botany, 2008)
Quality traits such as flavour and texture are assuming a greater importance in crop breeding programmes. This study takes advantage of potato germplasm differentiated in tuber flavour and texture traits. A recently developed 44,000-element potato microarray was used to identify tuber gene expression profiles that correspond to differences in tuber flavour and texture as well as carotenoid content and dormancy characteristics. Gene expression was compared in two Solanum tuberosum group Phureja cultivars and two S. tuberosum group Tuberosum cultivars; 309 genes were significantly and consistently up-regulated in Phureja, whereas 555 genes were down-regulated. Approximately 46% of the genes in these lists can be identified from their annotation and amongst these are candidates that may underpin the Phureja/Tuberosum trait differences. For example, a clear difference in the cooked tuber volatile profile is the higher level of the sesquiterpene alpha-copaene in Phureja compared with Tuberosum. A sesquiterpene synthase gene was identified as being more highly expressed in Phureja tubers and its corresponding full-length cDNA was demonstrated to encode alpha-copaene synthase. Other potential 'flavour genes', identified from their differential expression profiles, include those encoding branched-chain amino acid aminotransferase and a ribonuclease suggesting a mechanism for 5'-ribonucleotide formation in potato tubers on cooking. Major differences in the expression levels of genes involved in cell wall biosynthesis (and potentially texture) were also identified, including genes encoding pectin acetylesterase, xyloglucan endotransglycosylase and pectin methylesterase. Other gene expression differences that may impact tuber carotenoid content and tuber life-cycle phenotypes are discussed